Isolation and Differentiation of Mesenchymal Stem Cells From Broiler Chicken Compact Bones - Adhikari, Roshan; Chen, Chongxiao; Waters, Elizabeth; West, Franklin D.; Kim, Woo Kyun (Frontiers in Physiology, 2019)
Chicken mesenchymal stem cells (MSCs) can be used as an avian culture model to better understand osteogenic, adipogenic, and myogenic pathways and to identify unique bioactive nutrients and molecules which can promote or inhibit these pathways. MSCs could also be used as a model to study various developmental, physiological, and therapeutic processes in avian and other species. MSCs are multipotent stem cells that are capable of differentiation into bone, muscle, fat and closely related lineages and express unique and specific cell surface markers. MSCs have been isolated from numerous sources including human, mouse, rabbit, and chicken with potential clinical and agricultural applications. MSCs from chicken compact bones have not been isolated and characterized yet. In this study, MSCs were isolated from compact bones of the femur and tibia of day-old male broiler chicks to investigate the biological characteristics of the isolated cells. Isolated cells took 8-10 days to expand, demonstrated a monolayer growth pattern and were plastic adherent. Putative MSCs were spindle-shaped with elongated ends and showed rapid proliferation. MSCs demonstrated osteoblastic, adipocytic and myogenic differentiation when induced with specific differentiation media. Cell surface markers for MSCs such as CD90, CD105, CD73, CD44 were detected positive and CD31, CD34, and CD45 cells were detected negative by PCR assay. The results suggest that MSCs isolated from broiler compact bones (cBMSCs) possess similar biological characteristics as MSCs isolated from other chicken tissue sources.